Association between weekend catch-up sleep and glycemic control among individuals with diabetes: a population-based study - Wang, Peiqing; Li, Qiuling; Yu, Xiaojun; Wu, Lifeng; Liu, Jingyuan; Zheng, Yangxi; Liu, Zhenrui; Yao, Jieying; Fan, Sisi; Li, Yiqin (Frontiers in Endocrinology, 2025)
ObjectivesWeekend catch-up sleep (WCUS), a compensation for insufficient sleep during weekdays, was associated with desirable metabolic effects. However, its relationship with glycemic control among adults with diabetes was not fully established.MethodsParticipants from the 2017-2018 cycle of the National Health and Nutrition Examination Survey were included for analysis. WCUS was defined as a difference in sleep duration between weekends and weekdays of more than one hour. Glycemic control was assessed by hemoglobin A1C (HbA1c) and fasting plasma glucose levels. Poor glycemic control was defined as an HbA1c level exceeding 10.0%.ResultsThe final analysis included 571 participants (weighted number: 38,714,135), and 24.90% of them practicing WCUS. No significant association was found between glycemic control and the presence of WCUS. However, significant negative associations were noted between WCUS with a duration of 1-2 hours and HbA1c level [β= -0.82, 95% CI: (-1.34, -0.30), P=0.004] and fasting glucose level [β= -1.67, 95% CI: (-2.51, -0.82), P<0.001] when compared with participants with no WCUS, which remained consistent across different subgroups. In addition, it was also associated with a reduced risk of developing poor glycemic control (OR=0.10, 95% CI: (0.01, 0.60), P=0.015). With WCUS duration of ≥ 2 hours, such associations became not significant.ConclusionsWCUS for 1-2 hours was associated with lower levels of HbA1c and fasting glucose and reduced risk of developing poor glycemic control, while a duration of ≥ 2 hours was not. Further research is needed to determine the optimal duration of WCUS.